(untitled) (Technical Journal, 2023)
Maize shelling in developing and underdeveloped nations has been and remains a severe problem to its processing as it is tedious and requires more labour hours. This study aims to design and fabricate a motor-powered spike-shaft type Maize Seed Separator (MSS) machine. The design and selection of components like the motor, belt, frame, bearing, and shaft were made based on general design considerations. After the complete fabrication of the MSS machine, it was tested to find its shelling capacity and efficiency. The shelling capacity was found to be 220 kg/hr, which is 80 times faster than manual shelling and the maximum shelling efficiency was found to be 97 % at the feeding rate of 4 kg at a time. The machine consumes 1.28 kW of electricity, which, when operated for one hour,would cost about Rs. 14 per hour.